An Analytic-Critical Reading of the Book of the Nature of Islamic Art (A Collection of Essays and Lectures) - Ali asghar kalantar; Sadeq Rashidi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The aim of this article is to critically review the content and form of a book on Islamic Art (collection of essays and lectures). This book is one of the basic books on Islamic art discourse with different approaches. The authors of this book have sought to study the nature of Islamic art, through theoretical discussions in the context of historiographical, jurisprudential, mystical, sociological, semiotic, and hermeneutic attitudes. The main issue of this paper is to raise the fundamental question of how mystical and judgmental approaches to traditionalist discourse as well as historical approaches to descriptive discourse can analyze and interpret Islamic art and thus open the door to understanding and understanding the complexities of Islamic art discourse. We reveal the formation. The importance and critical importance of a critical look at Islamic art textbooks for a more detailed analysis as well as explaining the mechanisms and characteristics of the various approaches to Islamic art discourse analysis seem significant. For this reason, it is necessary to demonstrate the importance of the book in question by revealing its analytical functions aimed at guiding audiences and students concerned with Islamic art studies.